Squamous cell carcinoma of ear in an Indian water buffalo (Bubalus bubalis) - Devi, V. Rama; Veeraiah, G.; Annapurna, P.; Estheru, S. (Brazilian Journal of Veterinary Pathology, 2010)
A nine years old, Graded Murrah she buffalo was presented to local Veterinary dispensary with clinical signs of raised elevations of growths on the pinna of right ear near its base and lateral aspects showing ulceration, necrosis, scales, crusts and scabs. Histopathologically, the tissue sections from the growth revealed groups, islands or cords of neoplastic squamous epithelium with epithelial pearls at some places. By immunohistochemistry, proliferating epithelial cells were positive for cytokeratin and expressed PCNA. Based on gross, histologic and immunohistochemical findings, the growth was diagnosed as cutaneous squamous cell carcinoma of ear.